The Criminalistics Institute of the Belgrade Law Faculty, 1927-1945 - Janković Ivan (Pravni Zapisi, 2015)
The Institute's two goals were the scientific study of crime, on the one hand, and the forensic education of judicial and police personnel, on the other. Due to the influence of its founder, Professor Toma Živanović, the Institute was provided for, in terms of funding and premises, better than most University institutions. Nonetheless, its scholarly contribution to criminal science was negligible. As regards theoretical approaches, the Institute relied on the anachronistic Lombrosian ideas about the atavistic born criminal, as well as on the contemporary German school of criminal biology. Živanović's own 'realistic-psychological' theory, which postulated a 'criminal psychological state' (or: 'the criminal soul') as 'the immediate [causal] factor of crime', was never operationalized or empirically tested. The experiments conducted with the Institute's up-to-date and expensive equipment were mostly in the field of electrophysiology, corresponding to the interests of Živanović's closest collaborator, the Russian-born psychiatrist N.V. Krainsky. The Institute's contribution to the forensic education of police and court personnel may have been more substantial, although no sufficient data on its scope are available. Nothing was preserved of the Institute's laboratory equipment or of its archive.